Effective Stimulation Type and Waveform for Force Control of the Motor Unit System: Implications for Intraspinal Microstimulation - Kim, Hojeong; Ju, Youngchang (Frontiers in Neuroscience, 2021)
The input-output properties of spinal motoneurons and muscle fibers comprising motor units are highly nonlinear. The goal of this study was to investigate the stimulation type (continuous versus discrete) and waveform (linear versus nonlinear) controlling force production at the motor unit level under intraspinal microstimulation. We constructed a physiological model of the motor unit with computer software enabling virtual experiments on single motor units under a wide range of input conditions, including intracellular and synaptic stimulation of the motoneuron and variation in the muscle length under neuromodulatory inputs originating from the brainstem. Continuous current intensity and impulse current frequency waveforms were inversely estimated such that the motor unit could linearly develop and relax the muscle force within a broad range of contraction speeds and levels during isometric contraction at various muscle lengths. Under both continuous and discrete stimulation, the stimulation waveform nonlinearity increased with increasing speed and level of force production and with decreasing muscle length. Only discrete stimulation could control force relaxation at all muscle lengths. In contrast, continuous stimulation could not control force relaxation at high contraction levels in shorter-than-optimal muscles due to persistent inward current (PIC) saturation on the motoneuron dendrites. These results indicate that nonlinear adjustment of the stimulation waveform is more effective in regard to varying the force profile and muscle length and that the discrete stimulation protocol is a more robust approach for designing stimulation patterns aimed at neural interfaces for precise movement control under pathological conditions.